Recent Developments in Synthesis of xLi2MnO3 · (1 − x)LiMO2 (M = Ni, Co, Mn) Cathode Powders for High-Energy Lithium Rechargeable Batteries - Doan, The Nam Long; Yoo, Kimoon; Hoang, Tuan K. A.; Chen, P. (Frontiers in Energy Research, 2014)
Lithium-rich layered powders, Li2MnO3-stabilized LiMO2 (M = Ni, Co, Mn), are attractive cathode candidates for the next generations of high energy lithium-ion batteries. However, most of the state-of-the-art preparation procedures are complicated and require multiple energy-intensive reaction steps. Thus, elucidating a low-cost synthetic protocol is important for the application of these materials in future lithium-ion batteries. Recent developments in the synthesis procedures of lithium rich layered powders are discussed and future directions are pointed out in this review.